Tegumentary leishmaniasis in Northern Argentina: distribution of infection and disease, in three municipalities of Salta, 1990-1992 - Sosa-Estani Sergio; Segura Elsa Leonor; Salomón Oscar Daniel; Gómez Adolfo; Peralta Mario; Coutada Virgilio; Ruiz Luis Medina (Sociedade Brasileira de Medicina Tropical (SBMT), 2000)
This work describes the epidemiological pattern of tegumentary leishmaniasis in an area north of Salta, Argentina. The prevalence and incidence were estimated by means of a cross-sectional study and two follow-up studies during two consecutive years. The Montenegro Skin Test (MST) was administered to 7336 subjects at baseline. The prevalence and incidence between 1990 and 1992 of infection (MST reactive) was 38? persons and 4.5? persons/year respectively. The prevalence and incidence of tegumentary leishmaniasis (presence of clinical signs) was 1.8? and 0.8? persons/year, respectively. A physical examination performed on 264 patients with MST reactive during three years revealed that 130 cases (49.2%) had some evident sign of infection (scar and/or lesion), with a clinical presentation compatible with leishmaniasis. Our study demonstrated that after the epidemic outbreak of 1985 the transmission in the study area returned to endemic levels in 1992, and also demonstrated the presence of the asymptomatic infection in the area.